Development Of Historical Electronic Module On The Impact Of European Colonization For The Indonesian Nation For Senior High School - N Najuah; Ichwan Azhari; Pristi Suhendro Lukitoyo; Muhammad Ikhwal; Reny Sabrina Simamora (International Journal of Educational Research & Social Sciences, 2022)
This research is motivated by the fact that history learning in schools is still conventional and less innovative, such as still using the lecture method, Powerpoint, Video, and textbook oriented in teaching and learning activities at school. The objectives of this research are: (1) To develop the historical electronic module for Class XI SMA and (2) To determine the feasibility of the Historical Electronic Module Teaching Materials for Class XI SMA. This study uses a research and development model using the ADDIE development model which includes (1) Analysis, (2) Design, (3) Development, (4) Implementation. and (5) Evaluation (Evaluation). The subjects of this research include Material Expert Lecturers, Media Expert Lecturers, and Class XI Social Studies Students at SMA Swasta Cerdas Murni. The object of this research is a historical electronic module on the impact of European colonialism on the Indonesian people. The instruments used in this research are media expert validation instruments, material expert validation instruments, and student responses to the use of the historical electronic module. The results of this study indicate: (1) The development of the historical electronic module on the impact of European colonialism on the Indonesian people for class XI IPS SMA, (2) the historical electronic module is declared suitable for use as teaching materials in schools with an average score of material experts of 3.8 and the average score of media experts was 3.72, the average score of the medium group trial was 3.47 and the student response as users were 3.45 so that the feasibility of the historical electronic module developed was in the "very good category.